Analysis of Rare Variants in the Complement Component 2 (C2) and Factor B (BF) Genes Refine Association for Age-Related Macular Degeneration (AMD) - Richardson, Andrea J; Islam, F. M. Amirul; Guymer, Robyn H; Baird, Paul N (Investigative ophthalmology & visual science, 2009)
Several single-nucleotide polymorphisms (SNPs) in the C2 and BF genes have been associated with age-related macular degeneration (AMD) in Caucasian populations from the United States. The study was conducted to evaluate whether these SNPs are also associated with AMD in persons of Anglo-Celtic ethnicity in an Australian population. Included in the study were 565 persons with AMD and 204 ethnically matched control subjects. All participants completed a standard health questionnaire, were given a fundus examination, and provided a blood sample for DNA extraction. Alleles were determined by a matrix-assisted desorption ionization-time of flight (MALDI-TOF)-based approach followed by statistical analysis. The C2 and BF genes indicated significant association with AMD of only two SNPs; rs547154 (IVS10) in the C2 gene (P=9.1 x 10(-5)) and rs641153 (R32Q) in the BF gene (P=7.0 x 10(-5)). No association with AMD was found for SNP rs9332739 (E318D) in the C2 gene or for rs4151667 (L9H), rs1048709 (R150R), rs4151659 (K565E), or rs2072633 (IVS17) in the BF gene. A protective haplotype of variants IVS10 and R32Q was associated with AMD (OR 0.29, 95% CI 0.20-0.42). In this study, the association of the IVS10 and R32Q variants in the C2 and BF genes in AMD was replicated. Haplotype analysis indicated association of these variants with AMD in an Australian population. Both IVS10 and R32Q variants were in strong linkage disequilibrium with each other (r(2)=0.96). Although the E318D and L9H variants have shown association with AMD in previous studies, the findings were not in agreement. This demonstrates a refined pattern of association of these rare variants with AMD.